Mental Health Needs Due to Disasters: Implications for Behavioral Health Workforce Planning During the COVID-19 Pandemic. (May 2023) - Gaiser, Maria; Buche, Jessica; Baum, Nancy M.; Grazier, Kyle L.
Public health emergencies impact the well-being of people and communities. Long-term emotional distress is a pervasive and serious consequence of high levels of crisis exposure and low levels of access to mental health care. At highest risk for mental health trauma are historically medically underserved and socially marginalized populations and frontline health care workers (HCWs). Current public health emergency response efforts provide insufficient mental health services for these groups. The ongoing mental health crisis of the COVID-19 pandemic has implications for the resource-strained health care workforce. Public health has an important role in delivering psychosocial care and physical support in tandem with communities. Assessment of US and international public health strategies deployed during past public health emergencies can guide development of population-specific mental health care. The objectives of this topical review were (1) to examine scholarly and other literature on the mental health needs of HCWs and selected US and international policies to address them during the first 2 years of the pandemic and (2) to propose strategies for future responses. We reviewed 316 publications in 10 topic areas. Two-hundred fifty publications were excluded, leaving 66 for this topical review. Findings from our review indicate a need for flexible, tailored mental health outreach for HCWs after disasters. US and global research emphasizes the dearth of institutional mental health support for HCWs and of mental health providers who specialize in helping the health care workforce. Future public health disaster responses must address the mental health needs of HCWs to prevent lasting trauma.